PELATIHAN KONVERSI SKRIPSI MENJADI ARTIKEL ILMIAH UNTUK MENINGKATKAN KEMAMPUAN MENULIS MAHASISWA - Irianto Ibrahim; Andi Muh. Ruum Sya'baan; Fahruddin; Sulfiah; Marwati; La Ode Akhiri Zulzaman; Yustih Yasin (JESASI (JURNAL EDUKASI, SAINS, DAN INOVASI), 2024)
When students attempt to convert their thesis into a scientific article, they often face several challenges that require special attention. One of the main obstacles is the difference in writing style. A thesis generally employs a more informal and detailed writing style, while scientific articles demand a more formal and concise approach. Therefore, students need to make substantial revisions to their writing style to meet the standards of scientific publication. Additionally, structure also poses a challenge. Theses tend to have lengthy and sometimes overly detailed structures, whereas scientific articles typically follow a more streamlined and concise format. Students must reorganize their material to align with a structure commonly consisting of an introduction, literature review, methodology, results, discussion, and conclusion.